Pre-service teachers’ application of understanding by design in lesson planning - Ricardo Lumbreras, Jr.; William H. Rupley (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study focused on preservice secondary teacher’s use of the Understanding by Design (UbD), framework to create effective, engaging lessons for their future secondary level students. The subjects consisted of 69 secondary pre-service secondary education majors at a Texas University who were enrolled in a required course for admission into the teacher education program. Pre-posttest surveys of lesson knowledge design were administered to all subjects. Comparing pre- posttest results revealed that knowledge of lesson design showed improvement and knowledge gain in the following areas: concepts and vocabulary; unpacking standards; use of verbs from the standards; rigor; content objectives; formative assessment and summative assessment. The analyses made use of descriptive statistics and descriptions.